Diterpenoid constituents from sinularia maxima - Van Minh, Chau; Hoai Nam, Nguyen; Phuong Thao, Nguyen; Xuan Cuong, Nguyen; Van Thanh, Nguyen; Young Ho, Kim; Van Kiem, Phan (Vietnam Journal of Chemistry, 2015)
Three diterpenoids including isomandapamate (1), sethukarailin (2), and (1S,2E,4S,6E,8S,11R)-2,6,12(20)-cembratriene-4,8,11-triol (3) were isolated and structurally elucidated from the methanol extract of the soft coral Sinularia maxima by using combined chromatographic and spectroscopic experiments. Of the isolated compounds, 3 was isolated from S. maxima for the first time.